2021
DOI: 10.3389/fneur.2021.670610
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Components in Thrombi Retrieved by Thrombectomy for Internal Carotid Artery Occlusion Due to Large Artery Atherosclerosis: A Case Report

Abstract: Introduction: The correlation between the composition of thrombi retrieved by mechanical thrombectomy (MT) and stroke etiology is inconclusive. We describe a case with atherosclerotic components in thrombi retrieved by MT for acute internal carotid artery (ICA) occlusion.Case Presentation: A 69-year-old man with acute onset of global aphasia and right hemiplegia was transferred to our institute. His baseline National Institutes of Health Stroke Scale score was 24. Magnetic resonance imaging demonstrated acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The authors speculated that some thrombi with the varied findings were formed due to secondary blood stasis after initial vessel occlusion. 15) By contrast, in case 2, case 3 and ours, diagnosed as plaque embolism from thoracic aorta, foam cells and cholesterol crystals were mainly detected with very few hemocyte component. Their thrombus was readily retrieved within a short time after the onset without multiple attempts, and no significant vessel stenosis that might trigger embolism or blood stasis was noted.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The authors speculated that some thrombi with the varied findings were formed due to secondary blood stasis after initial vessel occlusion. 15) By contrast, in case 2, case 3 and ours, diagnosed as plaque embolism from thoracic aorta, foam cells and cholesterol crystals were mainly detected with very few hemocyte component. Their thrombus was readily retrieved within a short time after the onset without multiple attempts, and no significant vessel stenosis that might trigger embolism or blood stasis was noted.…”
Section: Discussionmentioning
confidence: 56%
“…[10][11][12] In our extensive research, we found and review four case reports of the retrieved thrombus containing cholesterol crystals in cerebral embolism (as summarized Table 1). 2,[13][14][15] Although all of them had atherosclerosis as the etiology and post-treatment was mainly oral antiplatelet agents, the pathogenesis can be primarily categorized as local thrombosis or plaque embolism.…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, macroscopic and pathological findings of emboli retrieved by mechanical thrombectomy can help to identify the embolic source. 3 Herein, we describe a patient with calcified cerebral embolism who had a cardiogenic embolic source. On the basis of macroscopic and pathological findings of the embolus retrieved by mechanical thrombectomy, we identified an atherosclerotic lesion with calcification as the embolic source and finally diagnosed an aortogenic calcified cerebral embolism.…”
mentioning
confidence: 99%